TIKTOK HADIS TENTANG MASUK ISLAM KARENA MENIKAH: ANALISIS KONTEN HUSEIN BASYAIBAN - Lestari, Faiza Puji (UNIVERSUM: Jurnal Keislaman dan Kebudayaan, 2023)
In this study analyzed the tiktok video regarding the issue of converting to Islam due to marriage made by Husain Basyaiban. the discussion discussed the study map of Husain Basyaiban's tiktok, a study of hadith on Husain Basyaiban's tiktok, a study of the issue of converting to Islam due to marriage on Husain Basyaiban's tiktok, the relevance of the study to the explanation of fiqh scholars. the aim is to find out the explanation regarding the issue of converting to Islam because of marriage and the meaning of the hadith about converting to Islam because of marriage and its relevance based on fiqh scholars. The methodology used is qualitative which explains from general to specific. Based on this research, it can be concluded that someone who converts to Islam and gets married, what needs to be punished is based on what appears. meaning that as a Muslim in this matter, what needs to be punished is that someone is Muslim and wants to strengthen his faith and believes that Rasulullah SAW is the last messenger. The hadith used to strengthen this issue is an authentic hadith and according to the opinion of fiqh scholars it is the same. so in this issue what needs to be judged is what appears. Husain Basyaiban's tiktok study contains several videos about the presentation of hadith which are then explained using a general view and according to fiqh scholars. In the content, Husain Basyaiban does not only discuss fiqh. However, it also discusses women's issues that are currently being discussed. In his interesting video, he talks about converting to Islam because he got married because this phenomenon is not only found today but has also been around for a long time. In this content, Husain stated that if there is someone who converts to Islam and then gets married, what needs to be known is that person has said two sentences of shahada which indicates that the person has converted to Islam, matters of his heart or faith are beyond human control. This was also explained by the fiqh scholars that as a Muslim it is better to only judge what appears to be about the heart beyond human control because the hadith that is used as a basis is an authentic hadith. Keywords: hadith, tiktok, converted to Islam because of marriage __________________________ Abstrak Pada penelitian ini menganalisis video tiktok mengenai isu masuk Islam karena menikah yang dibuat oleh Husain Basyaiban. pembahasan yang dibahas peta kajian tiktok Husain Basyaiban, kajian hadis pada tiktok Husain Basyaiban, kajian tentang isu masuk Islam karena menikah pada tiktok Husain Basyaiban, relevansi kajian dengan penjelasan ulama fiqih. tujuannya ialah untuk mengetahui penjelasan mengenai isu masuk Islam karena menikah dan pemaknaan hadis tentang masuk Islam karena menikah serta relevansi berdasarkan ulama fiqih. metodologi yang diguanakan adalah kualitatif yang menjelaskan dari umum ke khusus.berdasarkan penelitian tersebut dapat disimpulkan bahwa seseorang yang masuk Islam dan melangsungkan pernikahan maka yang perlu dihukumi adalah berdasarkan apa yang tampak. maksudnya sebagai seorang muslim dalam permasalahan ini maka yang perlu dihukumi adalah seorang tersebut Islam dan mau memperkuat keimanannya dan mempercayai bahwa Rasulallah SAW menupakan utusan terakhir. hadis yang digunakan untuk memperkuat isu tersebut merupakan hadis shahih dan menurut pendapat ulama fiqih juga demikian. sehingga dalam isu ini yang perlu dihukumi adalah apa yang tampak. Kajian tiktok Husain Basyaiban terdapat beberapa video tentang pemaparan hadis kemudian dijelaskan menggunakan pandangan secara umum dan menurut ulama fiqih. Dalam konten Husain Basyaiban tidak hanya membahas mengenai fiqih. Namun, juga membahas mengenai isu perempuan yang menjadi perbincangan di zaman sekarang. Dalam videonya yang menarik diabhas mengenai masuk Islam karena menikah karena fenomena tersebut bukan hanya ditemukan di zaman sekarang namun juga sudah ada sejak lama. Dalam konten tersebut Husain menyabutkan bahwa jika terdapat seorang yang masuk Islam kemuadian melangsungkan pernikahan maka yang perlu diketahui adalah orang tersebut telah mengucap dua kalimat syahadat yang menandakan bahwa seorang tersebut telah masuk Islam perihal hati atau keimanannya itu diluar kendali manusia. Hal ini juga dijelaskan oleh ulama fiqih bahwasannya sebagai seorang muslim maka baiknya hanya menghukumi apa yang nampak perihal hati itu diluar kendali manusia karena hadis yang digunakan sebagai sandarannya ialah hadis shahih.